Corporate Legal Liability for Failure to Register Workers in Indonesia's Social Security System: A Good Corporate Governance Perspective - I Made Upadana Putra Miasa; Made Aditya Pramana Putra (International Journal of Business, Law, and Education, 2026)
This article examines the legal consequences of a corporation's failure to register workers in Indonesia's national social security system and evaluates that non-compliance through the principles of Good Corporate Governance (GCG). It applies doctrinal legal research using statutory, conceptual, and analytical approaches. Primary legal materials include the 1945 Constitution, Law No. 40 of 2004 on the National Social Security System, Law No. 24 of 2011 on the Social Security Administering Bodies, Law No. 2 of 2004 on Industrial Relations Dispute Settlement, the labour-law framework as amended by Law No. 6 of 2023, and Government Regulation No. 86 of 2013. The analysis shows that the duty to register workers is a mandatory statutory obligation rather than a discretionary employee benefit. Failure to register directly attracts administrative sanctions and may also support a rights dispute and civil compensation where loss and causation are established. Criminal liability should not be inferred automatically from non-registration; under the BPJS Law it arises only when the specific statutory elements of contribution-related offences are satisfied. From a governance perspective, non-registration indicates failures of responsibility, accountability, fairness, transparency, board oversight, and internal control. The article develops an integrated liability-governance framework that connects legal sanctions with preventive corporate controls, including workforce reconciliation, contribution audits, board-level compliance reporting, accessible worker grievance procedures, and documented remediation. This framework clarifies the boundary between administrative, civil, industrial-relations, and criminal consequences while positioning social-security compliance as a core corporate-governance obligation.